Bradycardia‐to‐delivery interval and fetal outcomes in umbilical cord prolapse. (14th September 2020) - Wong, Lo; Tse, Wing T.; Lai, Chit Y.; Hui, Annie S. Y.; Chaemsaithong, Piya; Sahota, Daljit S.; Poon, Liona C.; Leung, Tak Y.
Abstract: Introduction: Umbilical cord prolapse is a major obstetric emergency associated with significant perinatal complications. However, there is no consensus on the optimal decision‐to‐delivery interval, as many previous studies have shown poor correlation between the interval and umbilical cord arterial blood gas or perinatal outcomes. We aim to investigate whether bradycardia‐to‐delivery or decision‐to‐delivery interval was related to poor cord arterial pH or adverse perinatal outcome in umbilical cord prolapse. Material and methods: This was a retrospective study conducted at a university tertiary obstetric unit in Hong Kong. All women with singleton pregnancy complicated by cord prolapse during labor between 1995 and 2018 were included. Women were categorized into three groups. Group 1: persistent bradycardia; Group 2: any type of decelerations without bradycardia; and Group 3: normal fetal heart rate. The main outcome was cord arterial blood gas results of the newborns in different groups. Maternal demographic data and perinatal outcomes were reviewed. Correlation analysis between cord arterial blood gas result and time intervals including bradycardia‐to‐delivery, deceleration‐to‐delivery, and decision‐to‐delivery were performed for the different groups with Spearman test. Results: There were 34, 30, and 50 women in Groups 1, 2, and 3, respectively. Cord arterial pH and base excess did not correlate with decision‐to‐delivery interval in any of the groups, but they were inversely correlated with bradycardia‐to‐delivery interval in Group 1 (Spearman's ρ   = −.349; P  = .043 and Spearman's ρ  = −.558; P  = .001, respectively). The cord arterial pH drops at 0.009 per minute with bradycardia‐to‐delivery interval in Group 1 (95% CI 0.0180‐0.0003). The risk of significant acidosis (pH < 7) was 80% when bradycardia‐to‐delivery interval was >20 minutes, and 17.2% when the interval was <20 minutes. Conclusions: There is significant correlation between bradycardia‐to‐delivery interval and cord arterial pH in umbilical cord prolapse with fetal bradycardia but not in cases with decelerations or normal heart rate. The drop of cord arterial pH is rapid and urgent delivery is essential in such situations.